2018
DOI: 10.1103/physrevb.98.125421
|View full text |Cite
|
Sign up to set email alerts
|

Quantum time mirrors for general two-band systems

Abstract: Methods that are devised to achieve reversal of quantum dynamics in time have been named "quatum time mirrors". Such a time mirror can be considered as a generalization of Hahn's spin echo to systems with continuous degrees of freedom. We extend the quantum time mirror protocol originally proposed for Dirac dispersions to arbitrary two-band systems and establish the general requirements for its efficient implementation. We further discuss its sensitivity to various nonhomogeneous perturbations including disord… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
(65 reference statements)
1
10
0
Order By: Relevance
“…Hence, we have shown that the ZB echo behaves as the quantum time mirror in Ref. [24] where for different band structures the effects of position-dependent potentials in the Hamiltonian, like disorder and electromagnetic fields are discussed additionally. To show that we recover the same results for the ZB echo also in these cases, we discuss the effect of disorder on the ZB echo in App.…”
Section: B Zb Echoes: Numericsmentioning
confidence: 77%
See 3 more Smart Citations
“…Hence, we have shown that the ZB echo behaves as the quantum time mirror in Ref. [24] where for different band structures the effects of position-dependent potentials in the Hamiltonian, like disorder and electromagnetic fields are discussed additionally. To show that we recover the same results for the ZB echo also in these cases, we discuss the effect of disorder on the ZB echo in App.…”
Section: B Zb Echoes: Numericsmentioning
confidence: 77%
“…For gapped Dirac systems the transition amplitude A s is independent of s, A s → A. One has [24] A(k, ∆t) = iκM…”
Section: A Zb Echoes: Analyticsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in a gravitycapillary wave field, a sudden change in the water wave speed (or gravity) can be easily generated by accelerating the water tank. Inspired by this new approach, many applications have emerged in different fields, e.g., spatiotemporal light control [12], signal filtration [13], full-duplex communication [14], wave scattering [15,16], temporal control of graphene plasmons [17], focusing beyond the diffraction limit [18,19], and negative refraction [20,21] among others [22,23]. Recently, the ITM protocol is also introduced into quantum systems, generating wave function echoes with high fidelities [24].…”
Section: Introductionmentioning
confidence: 99%